Sequela after ocular trauma by injection needle - Mrugacz, Małgorzata; Falkowski, Stanisław; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
We present a case of patient with ophthalmological changes after ocular trauma by injection needle.